Adaptación de lente de contacto rígido en paciente masculino de 21 años con queratocono. - Lapo Espinoza, Grace Paola (2023)
This case study presents the fitting of a rigid contact lens in a 21-year-old male patient with keratoconus. The patient arrives at the optometric consultation after being referred by the corneologist for the adaptation of the contact lens (LC). He refers to having started treatment with an ophthalmic antihistamine and artificial tears a month ago due to allergic conjunctivitis and dry eye. After evaluating the corneal tomography, it was decided to adapt a contact lens in the left eye since it did not improve with optical correction, it presented a stage III according to Belin's ABCD classification and also because of the patient's economic situation. The right eye presents stage I keratoconus. Visual acuity was taken, refraction with retinoscopy, autorefractometer, and finally biomicroscopy. It was decided to adapt a rigid gas permeable contact lens (LC RPG) in the left eye and additionally a frame lens to compensate for the ametropia of the right eye. During adaptation, fluorograms are performed to observe the behavior of the lens and determine the base curve of the lens. In two more sessions, the adaptation of the lens is evaluated, in addition to a control for allergic conjunctivitis and dry eye. The LC RPG improved the visual quality of the patient and provided visual comfort during the 8 hours of its use. The final recommendations were to maintain adequate lens cleaning and perform a corneal tomography in 6 months to assess the progression of keratoconus.